2014
DOI: 10.1104/pp.113.234310
|View full text |Cite
|
Sign up to set email alerts
|

Functional Convergence of Oxylipin and Abscisic Acid Pathways Controls Stomatal Closure in Response to Drought    

Abstract: Membranes are primary sites of perception of environmental stimuli. Polyunsaturated fatty acids are major structural constituents of membranes that also function as modulators of a multitude of signal transduction pathways evoked by environmental stimuli. Different stresses induce production of a distinct blend of oxygenated polyunsaturated fatty acids, "oxylipins." We employed three Arabidopsis (Arabidopsis thaliana) ecotypes to examine the oxylipin signature in response to specific stresses and determined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
172
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(195 citation statements)
references
References 55 publications
13
172
0
1
Order By: Relevance
“…This finding suggests that OPDA might participate in the mechanisms that confer tolerance to water stress in B71 seedlings (Andrade, unpublished data). In concordance, [41] demonstrated that Arabidopsis plants producing higher OPDA levels exhibited a reduction in the stomatal aperture, and as result enhanced drought tolerance (Figure 2). It should be pointed out that this study confirmed OPDA as a drought-responsive regulator of stomatal closure which might act effectively together with ABA in this response.…”
Section: Effect Of Ja On Plant Growth Responses Under Drought and Salsupporting
confidence: 63%
“…This finding suggests that OPDA might participate in the mechanisms that confer tolerance to water stress in B71 seedlings (Andrade, unpublished data). In concordance, [41] demonstrated that Arabidopsis plants producing higher OPDA levels exhibited a reduction in the stomatal aperture, and as result enhanced drought tolerance (Figure 2). It should be pointed out that this study confirmed OPDA as a drought-responsive regulator of stomatal closure which might act effectively together with ABA in this response.…”
Section: Effect Of Ja On Plant Growth Responses Under Drought and Salsupporting
confidence: 63%
“…In particular, methylated JA (MeJA) has been used extensively to elucidate JA-dependent responses. Although some studies have provided evidence that MeJA closes the stomatal pore (Suhita et al, 2004;Munemasa et al, 2007;DesclosTheveniau et al, 2012;Hua et al, 2012;Yan et al, 2015), this could not be verified by other research groups (Speth et al, 2009;Savchenko et al, 2014). This inconsistency might be explained by the fact that an endogenous ABA threshold is needed for MeJA-induced stomatal closure (Hossain et al, 2011).…”
Section: Recognition Of Bacteriamentioning
confidence: 95%
“…Froehlich et al (2001) showed that tomato HPL and AOS are targeted to the outer and inner membranes of the chloroplast envelope, respectively. Rice HPL3 (OsHPL3), which has the shortest extension of its N-terminal among the three HPLs, was transported to chloroplasts when a fusion protein of the transit peptide of OsHPL3 with green fluorescent protein (GFP) was expressed in Arabidopsis leaves (Savchenko et al 2014). However, localization of HPL in Arabidopsis has not been reported.…”
Section: Introductionmentioning
confidence: 99%